The Causative Organisms of Neonatal Sepsis in Al-Kadhimiyia Teaching Hospital (Iraqi Journal of Medical Sciences, 2016)
Background:Sepsis is common in the neonatal period which may be acquired in utero through the placental or trans-cervical routes and during or after birth and because the immunological system of neonates is not well developed which make this infection serious and fatal if not treated in accurate manner.Objective:To identify the most common causes of sepsis in Al-Kadhimiya Teaching Hospital and its mortality rate.Methods:Across-sectional study was conducted during the period between 14th of February 2009 to 25th of February 2010 on 127 neonates with sepsis who were diagnosed clinically and they were admitted in Al-Kadhthimyia Teaching Hospital, they were divided into two groups according to the time of appearance of the symptoms which were early onset sepsis and late onset sepsis. Blood was taken from them and sends to Hospital laboratory for culture.Results:The most common clinical presentation in early onset sepsis (EOS) were, poor feeding, lethargy and fever (94.12%, 91.76 %, and 52.94 %, respectively), which is similar to late onset sepsis (LOS) (95.24 %, 92.86 % and 57.14 % respectively). The most common organisms responsible for EOS were Staph. aureus, Enterobacteria, and staph. epidermidis (25.89 %, 21.18 % and 21.18 %, respectively) while in LOS Staph. aureus, Enterobacteria and E. coli (21.43 %, 16.67 % and 11.90 %). The overall mortality was 29.92 % which was slightly more in LOS (30.95 %) than in EOS (29.41%) also it was more common in males than females in both groups.Conclusion:Staph. aureus, Enterobacteria were the leading causes of sepsis in both groups while staph. epidermidis were more common in EOS and E. coli was more common in LOS.Key words:Early onset, late onset, sepsis, neonate
Keywords: Early onset; late onset; sepsis; neonate